Modelling the determinants of unemployment exit duration among graduates in a fragile state: a case of Somalia - Ali, Dahir Abdi; Mohamed, Jama; Midi, Habshah (Adonis and Abbey Publishers, 2022)
The scale of the severity of graduate unemployment in a fragile state like Somalia prompts the need for modelling factors related to the unemployment exit duration. Hence, this study aimed to model the determinants of graduate unemployment exit duration. More specifically, it determined the factors that have effects on the probability of escaping from the unemployment status. Data collected from students who graduated from SIMAD University in Somalia were analysed, using the duration model. Particularly, this paper utilised product-limit estimator and Cox proportional hazards model to model the prognostic factors influencing the probability of leaving the unemployment status. Gender, CGPA, part-time job experience, type of degree, and age were found to have significant effects on the probability of escaping from unemployment. Male graduates were 1.47 times more likely to increase their chances of employability than their female counterparts while graduates with part-time job experience were 2.81 more likely to escape from unemployment than graduates without part-time job experience. Similarly, graduates with a higher CGPA were 1.54 times more likely to get employment than those with a low CGPA.